Impelentasi Layanan Konseling Kelompok Pendekatan Realita Teknik WDEP untuk Meningkatkan Self Confidence Siswa Kelas X DPB SMK Negeri 4 Denpasar - Yuliastini, Ni Komang Sri; Aulia, Nissa; Satriadi, M. (Journal Prakarsa Paedagogia, 2024)
One of the factors supporting student learning outcomes is related to their self-confidence. By applying reality approach counseling with the WDEP technique, it is a form of intervention that focuses on finding solutions to solve problems. The aim of this research is to measure the level of success in the implementation of the WDEP Technique Reality Approach Group Counseling Service to Increase Students' Self Confidence. This research uses a classroom action research method with 8 subjects. The research was carried out through 2 cycles. The tool used is an observation tool to measure students' self-confidence. Data analysis was carried out qualitatively by describing the facts collected and presenting them in the form of descriptions. The result of this research is that there is an increase in self-confidence in students after being provided with group counseling services using the WDEP technique reality approach.